Collidescope - Chetwin, Grace (New York : Bradbury Press, 1990)
When his spaceship crashes to earth, a highly advanced alien interferes with the lives of two teenagers living on the island of Manhattan during different centuries.
Includes bibliographical references.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.7
6.7
Keywords: Extraterrestrial beings -- Fiction; Science fiction; Time travel -- Fiction; Extraterrestrial beings -- Fiction; Science fiction; Space and time -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction